A Book of Conquest - Asif, Manan Ahmed (Harvard University Press, 2016)
Cover -- Title -- Copyright -- Dedication -- Contents -- List of Illustrations -- Note on Transliteration and Translation -- Introduction -- Chapter 1. Frontier with the House of Gold -- Chapter 2. A Foundation for History -- Chapter 3. Dear Son, What Is the Matter with You? -- Chapter 4. A Demon with Ruby Eyes -- Chapter 5. The Half Smile -- Chapter 6. A Conquest of Pasts -- Conclusion -- Notes -- Works Cited -- Acknowledgments -- Index